High Rates of STIs in HIV-Infected Patients Attending an STI Clinic. Issue 1 (January 2016) - Castro, Jose G.; Alcaide, Maria Luisa
Abstract : Objectives: To evaluate the rates and types of sexually transmitted infections (STIs) in patients infected with the human immunodeficiency virus (HIV) attending a public STI clinic in Miami, Florida as compared with HIV-uninfected patients attending the same clinic. Methods: This was a retrospective review of medical records of individuals attending the Miami-Dade County Health Department STI clinic from March 2012 to May 2012. Demographic and clinical information was abstracted and transferred to an electronic database. Consecutive age-matched HIV-infected and HIV-uninfected patients were identified during the study period. Demographics, risk factors, and history and rates of STIs for HIV-infected and HIV-uninfected patients and for those with newly diagnosed and previously diagnosed HIV infection were compared. Results: A total of 175 medical records were reviewed (89 HIV-infected patients and 86 HIV-uninfected patients). The median age was 37 years. A history of STIs, including syphilis, was more common in HIV-infected than in HIV-uninfected patients. Individuals with a prior diagnosis of HIV were more likely to be older (older than 37 years of age, χ 2 = 15.3, P < 0.01), male (χ 2 = 4.74, P = 0.05), to have a new STI (χ 2 = 5.83, P = 0.01), to have a new diagnosis of syphilis (χ 2 = 5.15, P = 0.01), and to be under medical care (χ 2 = 31.19, P < 0.001) than those newly diagnosed as having HIV. Conclusions: HIV-infected individuals who attended this urban STI clinic had high rates of new and past STIs, suggesting the persistence of high-risk sexual behaviors. STI clinics could be a premier site to identify individuals with HIV and high-risk sexual behaviors who could benefit from additional targeted interventions. Abstract : This article describes the rates of sexually transmitted infections (STIs) in patients with the human immunodeficiency virus (HIV) who attended a health department STI clinic in Miami, Florida. The high rates of new and past STIs in HIV-infected individuals who attend this clinic suggest the persistence of high-risk behaviors. This report highlights the urgent need to develop interventions aimed to decrease high-risk sexual behaviors in a core group of HIV-infected people. It also provides evidence of real-world consequences of the imperfect continuum of care of people infected with HIV.